2019
DOI: 10.3390/ijms20092179
|View full text |Cite
|
Sign up to set email alerts
|

How to Steer and Control ERK and the ERK Signaling Cascade Exemplified by Looking at Cardiac Insufficiency

Abstract: Mathematical optimization framework allows the identification of certain nodes within a signaling network. In this work, we analyzed the complex extracellular-signal-regulated kinase 1 and 2 (ERK1/2) cascade in cardiomyocytes using the framework to find efficient adjustment screws for this cascade that is important for cardiomyocyte survival and maladaptive heart muscle growth. We modeled optimal pharmacological intervention points that are beneficial for the heart, but avoid the occurrence of a maladaptive ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…As a result, we have that based on the data our model cannot be rejected (subsequently shown) and thus the model, in particular the topology of the interaction network, with the fitted parameters can be used as an explanation for the experiment investigating the connection between cGMP turnover and drug concentration for platelets. Furthermore it is reasonable to use the model for further in silico investigations, for example with the optimization framework presented in Breitenbach et al (2019a,b) for optimal dosage calculations or for finding most effective drug combinations in silico .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, we have that based on the data our model cannot be rejected (subsequently shown) and thus the model, in particular the topology of the interaction network, with the fitted parameters can be used as an explanation for the experiment investigating the connection between cGMP turnover and drug concentration for platelets. Furthermore it is reasonable to use the model for further in silico investigations, for example with the optimization framework presented in Breitenbach et al (2019a,b) for optimal dosage calculations or for finding most effective drug combinations in silico .…”
Section: Resultsmentioning
confidence: 99%
“…Once the model is set up and describes the data curves sufficiently well, i.e. the model cannot be rejected, we can further exploit the information coded in the fitted mathematical model by an optimization framework presented in Breitenbach et al (2019a,b) in order to calculate an optimal drug dosage or most effective drug combinations for a desired cGMP concentration or for steering the concentration time-resolved along a desired cGMP concentration curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence and development of cardiac hypertrophy is also accompanied by the abnormal activation of a large number of important signaling pathways ( 5 , 39 , 40 ). Consequently, there is an increased level of interest in how key signaling pathways participate in the epigenetic regulation of cardiac hypertrophy ( 41 , 42 ). Our previous studies found that an imbalance of histone acetylation modification is involved in PE-induced hypertrophy in cardiomyocytes, and that an HAT inhibitor, AA, can attenuate PE-induced cardiomyocyte hypertrophy ( 4 ); however, the relevant upstream signaling pathways have yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, these approaches will always be necessary because of the simplified process established in a largely isolated system and temporal relationships. More recently, a new method, known as mathematical optimization framework, also analyzed the complex ERK1/2 cascade in cardiomyocytes to find efficient adjustment screws for this cascade that is important for cardiomyocyte survival and maladaptive heart muscle growth [19].…”
Section: Introductionmentioning
confidence: 99%